Two-staged uplift of the southeast margin of the Tibetan plateau revealed by river longitudinal profiles - Pan, Rouxian; Han, Zhiyong; Su, Qi; Li, Guangwei; Li, Xusheng; Li, Yalin; Wang, Xianyan (Frontiers in Earth Science, 2023)
The Jinsha River, upstream of the Yangtze River, flows through the southeastern margin of the plateau, providing an opportunity to study the plateau uplift relative to the Sichuan basin through fluvial geomorphology. Eight tributaries of the Jinsha River located at the transition boundary from the plateau to the basin were analyzed for the feature of longitudinal profile and its evolution. The spatial distribution of slope-break knickpoints in the catchment was determined by slope-area analysis and integration analysis. Further, the magnitude and timing of the base level lowering (i.e., uplift of the Tibetan Plateau) were estimated by reconstructing the river longitudinal profile. The results show that there are two levels of slope-break knickpoints, with average elevations of 2865 m and 1523 m, corresponding to base levels relatively lowering of 1400 m and 1100 m, respectively. With reference to the long-term downcutting rate of the Jinsha River, the timings of these two phases base level lowering and uplifts are estimated to be ∼21–24 and ∼7–13 Ma, respectively. These are close to the timing of two uplifts revealed by inversion modeling of river longitudinal profiles. Therefore, the uplift of the studied region on the Tibetan Plateau can be divided into two stages, the early stage (∼20 Ma) uplift from 1500 to 2900 m and the late stage (∼10 Ma) uplift from 2900 to 4000 m, which further supports the staged outside uplift of the Tibetan Plateau.